KARAKTERISTIK HABITAT TAPIR ASIA (Tapirus indicus) WILAYAH KERJA RESORT LAHAI SPTN II BELILAS TAMAN NASIONAL BUKIT TIGA PULUH DAN SEKITARNYA DI PROVINSI RIAU - khairul anwar; Defri Yoza; Viny Volcherina Darlins (Fakultas Pertanian, Universitas Riau, 2023)
Tapir is a large endemic mammal on the Sumatra island, this animal is prioritized for conservation because it is categorized as an endangered species. The population is at risk of extinction >20% over a 20 year period, when no conservation efforts are made in accordance with their habitat. Tapirs can live in swamp habitats, lowlands, mountains, hilly forests, secondary forests, shrubs and palm plantations. All of the most important types of habitat are the availability of food, water and shelter. A habitat that is suitable for the survival of the tapirs is needed, such as the availability of sufficient food and an environment that supports tapirs to breed. This research aims to find out the characteristics of Asian tapir habitat (Tapirus indicus) in several types of primary forest vegetation, secondary forests and shrubs in the working area of Resort Lahai SPTN II Belilas Bukit Tiga puluh National Park and surrounding areas in Riau Province. This research was conducted using purposive sampling method by determining the characteristics of tapir habitat. The characteristic of tapir habitats in TNBT and surrounding areas in the three vegetation are the closure of tree headers in the bush 0%, secondary forests 3.63%-54.21% and primary forests 4.37%-85.66%. Availability of feed plants in primary forests 3.03%-83.33%, secondary forests 39.13%-100.00%, shrubs 50.00%-100.00%. The characteristic of tapir habitats in primary forests, Secondary forests and shrubs include low land with topography ramps up to rather steep, distances with natural forests from primary forests are 633.54 m-1,155.00 m, secondary forests 1,253.32 m-1,791.76 m and shrubs 1,539.76 m-1,985.14 m. Distance by river from secondary forest 100.84 m-325.95 m, primary forest 126.58 m-290.99 m and shrub 111.33 m-356.04 m.